Analis Faktor Penentu Niat Digipreneurship Mahasiswa: Perspektif Model Peristiwa Kewirausahaan dan Teori Determinasi Diri - Hadi, Antonius Satria (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), 2025)
Entrepreneurship is believed to create job opportunities and drive economic growth. Entrepreneurial spirit represents one of the most significant economic developments in business history. New businesses established by entrepreneurs contribute to market expansion and play a crucial role in national economic development. This study aims to examine the influence of the Entrepreneurial Event Model and Self-Determination Theory on students' interest and commitment to digipreneurship. The study proposes four hypotheses: perceived desirability affects interest in digipreneurship, the propensity to act influences interest in digipreneurship, perceived feasibility partially affects interest in digipreneurship, and interest in digipreneurship impacts commitment to digipreneurship. Data were collected from 100 respondents through an online questionnaire distributed to students in Yogyakarta who are enrolled in entrepreneurship programs or have completed entrepreneurship courses, using a purposive sampling technique. The data were then analyzed using SmartPLS. The findings of this study are expected to provide strategic insights that universities can implement to further enhance students' motivation to pursue entrepreneurial ventures.